The effectiveness of canteen manager audit and feedback reports and online menu-labels in encouraging healthier food choices within students' online lunch orders: A pilot cluster randomised controlled trial in primary school canteens in New South Wales, Australia. (1st February 2022) - Wyse, Rebecca; Jackson, Jacklyn; Stacey, Fiona; Delaney, Tessa; Ivers, Alix; Lecathelinais, Christophe; Sutherland, Rachel
Abstract: Online school canteen lunch ordering systems may offer a unique opportunity to support the implementation of school canteen nutrition polices, while delivering behavioural interventions directly to consumers to influence healthy student purchasing. This cluster randomised controlled trial aimed to test the effectiveness of a menu audit and feedback strategy alone, and in combination with online menu labels in encouraging healthier purchasing from an online school canteen ordering system. Five intervention schools received a menu audit and feedback strategy, plus online menu labels; and five control schools received a delayed menu audit and feedback strategy. Data from 19, 799 student lunch orders, containing over 40, 000 items were included in the evaluation. Outcomes were assessed at baseline (pre-intervention), follow-up 1 (menu audit and feedback vs control), and follow-up 2 (menu audit and feedback plus online menu labels vs menu audit and feedback alone). From baseline to follow-up 1, the menu audit and feedback strategy alone had no significant effect on the proportion of healthy ('Everyday') and less healthy ('Occasional' or 'Should not be sold') items purchased. From baseline to follow-up 2, schools that received menu audit and feedback plus online menu labels had significantly higher odds of students purchasing 'Everyday' items (OR: 1.19; p = 0.019), and significantly lower odds of students purchasing 'Occasional' (OR: 0.86; p = 0.048) and 'Should not be sold' (OR: 0.52; p < 0.001) items. Menu audit and feedback with the addition of online menu labels was effective in increasing the proportion of healthy items purchased relative to menu audit and feedback in isolation. There may be a greater role for online menu labelling as part of a suite of strategies to improve public health nutrition in schools.